Hydroxyapatite/hydroxyapatite-magnesium double-layer coatings as potential candidates for surface modification of 316 LVM stainless steel implants. Issue 16 (November 2020) - Rezaei, Alireza; Golenji, Raouf Behjat; Alipour, Fardin; Hadavi, Mohammad Mahdi; Mobasherpour, Iman
Abstract: Various methods are being used for surface modification of orthopedic and dental implants such as deposition of biocompatible coatings on implant surfaces. In this study, hydroxyapatite/hydroxyapatite-Mg double-layer coatings applied on 316 LVM stainless steel are investigated. The applied coatings consist of a dense layer of plasma-sprayed hydroxyapatite and a top layer of cold-sprayed hydroxyapatite-magnesium composite coating (Mg = 10 and 30 wt%). The coated samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) tests. The biological behaviors of the coated samples were evaluated by immersing the samples in a simulated body fluid (SBF) followed by inductively coupled plasma (ICP) spectroscopy, MTT and electrochemical tests. Microstructural studies of the coated samples after corrosion tests showed that the magnesium component of the top layer degraded in SBF solution and formed porosities, which are potential sites for bone tissue growth. Results of ICP spectroscopy analysis indicated that the applied double-layer coating systems prevent the release of toxic elements in the substrate such as nickel. Results of MTT and SBF immersion tests showed that the double-layer coating system improves the biocompatibility and bioactivity of 316 LVM stainless steel.